Painful 20 fingers' onychodistrophy - Michele Bertero; Zelda Seia; C Del Grande; L Musso; S Palazzini (Wolters Kluwer Medknow Publications, 2011)
Psoriatic onycho-pachydermo-periostitis (POPP) is a rare subset of psoriatic arthritis. It is usually localized to the hands and it is characterized by onychodistrophy, soft tissue thickening above the distal phalanx and periosteal reaction. The resolution is very slow due to the involvement of nails and bone. Low dose methotrexate and anti-tumor necrosis factor-α (anti-TNF-α) agents are the suggested therapies. We report a case of a 53-year-old man affected by palmo-plantar slight psoriatic dermatitis, who presented a rapid onset of POPP. Rx imaging showed enthesitis and a moderate phalanx erosion with articular spaces narrowing and swollen periosteal reaction. A magnetic resonance imaging test of the hands showed an initial stage of synovitis and extensive periostitis of the distal phalangeal tufts. The patient has been treated with oral methotrexate for a month with a rapid clinical improvement and pain reduction. As POPP at first manifests as a painful onycodistrophy, it can easily be confused with bacterial perionyxis. The delay in making the correct diagnosis, and therefore, the delay in giving a proper treatment would mean the progressive articular erosion and the permanent invalidation of the patient's ability to use his hands.